Wrongful Life, Wrongful Birth, and Justice in Tort Law - Patrick J. Kelley (Washington University Law Quarterly, 1979)
Should those who undertake to aid couples in preventing the birth of a child by contraception or abortion be liable in tort for damages when something goes wrong and an "unwanted" child is born?
Keywords: Parent and child; Physicians and surgeons; Torts